A tunable diode laser absorption spectroscopy (TDLAS) signal denoising method based on LSTM-DAE - zhao, Peng; Ding, Dan; Li, Kaitai; Li, Ye; Jin, Guangyong (Optics communications, 2024)
The second harmonic signal serves as the informational foundation for the inversion of the gas concentration in the tunable diode laser absorption spectroscopy (TDLAS) detection method. However, due to the impact of noise on the second harmonic signal, the accuracy and stability of the detection system are decreased. In this paper, a digital denoising method based on Long Short-Term Memory Denoising Autoencoder (LSTM-DAE) is proposed to address the issue of multiple noise interference in TDLAS detection system. In LSTM-DAE, the conventional DAE is combined with LSTM structure. The second harmonic signal has time correlation, and the LSTM structure can selectively remember the past node state, which helps the DAE reconstruct the original data. Additionally, CO2 absorption spectrum at 2004 nm as an example, the effectiveness of this method is confirmed through simulated and real experiments. The experimental results demonstrate that LSTM-DAE, with the signal-to-noise ratio of 46.65 dB, the correlation coefficient of 0.9983, and the system detection limit of 6.1 ppb, outperforms other competitive methods in both qualitative and quantitative evaluations.